2014
DOI: 10.1161/circulationaha.113.003126
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Venous Thromboembolism in Patients Hospitalized With Heart Failure

Abstract: Background-Whether heart failure (HF) increases the risk of venous thromboembolism (VTE) is not well established.In the phase III MAGELLAN (Multicenter, rAndomized, parallel Group Efficacy and safety study for the prevention of venous thromboembolism in hospitalized medically iLL patients comparing rivaroxabAN with enoxaparin) trial, extended-duration rivaroxaban was compared with standard-duration enoxaparin followed by placebo for VTE prevention in 8101 hospitalized acutely ill patients with or without HF. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…15 Similarly, warfarin was associated with a lower rate of stroke compared with aspirin or clopidogrel in the Warfarin and Antiplatelet Therapy in Chronic Heart Failure trial. 16 Although the establishment of cutoff values and optimal strategies for VTE prophylaxis were beyond the scope of the work by Mebazaa et al, 11 the study clearly points toward particular use of rivaroxaban in patients with more severe heart failure for the prevention of short-term or medium-term VTE risks. Although clinical signs alone appear to be sufficient to identify patients with more severe forms of heart failure who may benefit from more (intense?)…”
Section: Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Similarly, warfarin was associated with a lower rate of stroke compared with aspirin or clopidogrel in the Warfarin and Antiplatelet Therapy in Chronic Heart Failure trial. 16 Although the establishment of cutoff values and optimal strategies for VTE prophylaxis were beyond the scope of the work by Mebazaa et al, 11 the study clearly points toward particular use of rivaroxaban in patients with more severe heart failure for the prevention of short-term or medium-term VTE risks. Although clinical signs alone appear to be sufficient to identify patients with more severe forms of heart failure who may benefit from more (intense?)…”
Section: Circulationmentioning
confidence: 99%
“…However, data from randomized trials specifically devoted to this high-risk population would be required to provide robust evidence for their routine clinical use. The study by Mebazaa et al 11 gives an excellent justification for such a randomized trial.…”
Section: Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the NT-proBNP is suggested to be useful to identify high short-term (Day 10) risk and elevated D-dimer may be useful in recognizing high midterm (Day 35) risk [26]. Elevated NT-proBNP concentration is supposed to be an independent predictor of recurrent VTE in a Chinese study [27], but the result is not consistent with data from the Acute Decompensated Heart Failure National Registry, which indicate that the BNP levels in patients aged ≥65 years is not associated with an increased risk of thromboembolism [28].…”
Section: Risk Factor and Incidencementioning
confidence: 99%
“…Patients with obesity, congestive heart failure (CHF), chronic obstructive pulmonary disease (COPD), and sickle-cell disease are at higher risk of VTE compared with other medical patients. 2,3 Most hospitalized patients on bed rest should be given prophylactic therapy unless specific contraindications exist.…”
Section: Vte Prophylaxis In Hospitalized Medical Patientsmentioning
confidence: 99%